Home buyers’ perception on abandoned housing projects in Malaysia - Abdul Razak, Dzuljastri; Abu Samah, Zariah; Abdul Wahab, Abdul Hamid (Zes Rokman Enterprise, 2016)
Abandoned housing project has become a major issue in the housing industry in Malaysia. Despite several efforts by the government to curb the problem, it still exists in the country. The current study offer new insights on the perceptions of home buyers concerning abandoned housing projects in Malaysia. Two Islamic home financing products that is Bai Bithaman Ajil (BBA) and Musharakah Mutanaqisah Partnership (MMP) are considered. The objective is to determine based on the opinion of the respondents, which one is more preferred. In addition, what are some of the potential causes of abandoned housing projects in Malaysia. The perception of home buyers are evaluated based on five variables namely , financing concepts used, justice and fairness, pricing methods, legal and governance, and shari’ah compliance issues. The findings show that, using MMP concept in Islamic home financing is preferred as compared to BBA. Furthermore, insufficient laws and regulations and the use of BBA financing are viewed to be some of the contributing factors that causes abandoned housing projects in Malaysia Keywords: Bai Bithaman Ajil, Musharakah Mutanaqisah Partnership, Justice Abandoned housing projects, Malaysia